The Influence of Influencer Marketing and Product Differentiation on Skincare Purchasing Decisions on Instagram Among Generation Z in Medan City: Pengaruh Influencer Marketing Dan Diferensiasi Produk Terhadap Keputusan Pembelian Skincare Di Instagram Pada Kalangan Generasi Z Di Kota Medan - Vasco Mario Prasetio; Pesta Gultom (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the influence of influencer marketing and product differentiation on the decision to purchase skincare products among Generation Z who actively use Instagram in a major city, namely Medan. The method used is quantitative research with data collection through questionnaires distributed to respondents who meet the criteria of age, skincare user characteristics, and Instagram users. The results of the study indicate that both variables have a significant positive influence on purchasing decisions. Influencer marketing has been proven to be effective in building trust and influencing purchasing decisions, while unique and value-added product differentiation attracts consumers in a competitive market. The implications of these findings suggest that integrating influencer marketing strategies and product differentiation can be an effective approach for marketers in designing more focused and relevant campaigns, especially for young consumer segments that are highly influenced by social media. This research provides important insights into the development of marketing strategies in the dynamic digital era.